PENGARUH BERBAGAI DOSIS CENDAWAN ANTAGONIS Trichoderma spp.UNTUK MENGENDALIKAN PENYAKIT LAYUFusarium oxysporum PADA TANAMAN TOMAT - Rosmini, Johanis Panggeso, I Made Susila Antara (AGROTEKBIS, 2015)
One of the diseases that exist and are very detrimental to farmers wilt disease caused by the fungus Fusarium oxysporum on tomato plants, where the disease is an important disease and including major diseases on tomato plants. The level of pathogenic attack caused substantial losses to farmers. The aim of research to determine the effect of the fungus Trichoderma spp. in suppressing the development of Fusarium wilt disease in relation to the optimal plant growth and yield of tomato. This study aims to determine the effect of the fungus Trichoderma spp. in suppressing the development of Fusarium oxysporum disease in relation to growth and optimal results on tomato plants. This study was conducted in September 2014 until the month of February 2015, at the Laboratory of Plant Pests and Diseases and Greenhouse, Faculty of Agriculture, University of Tadulako. Research using completely randomized design (CRD) consisting of 5 treatments, T1 = control (without application), T2 = treated Trichoderma spp. as much as 20 g / polybag, T3 = treatment of Trichoderma spp. as much as 30 g / polybag, T4 = treated Trichoderma spp. as much as 40 g / polybag and T5 = treated Trichoderma spp. as much as 50 g / polybag. Each treatment was repeated five times so that there are 25 experimental units. The results showed the introduction of the fungus Trichoderma spp. In polybag can suppress Fusarium oxysporum disease progression and sustain growth (plant height) as well as the results (number and weight of fruit) tomato plants.